DEVELOPING CONDUCTING SKILLS IN STUDENTS THROUGH MUSIC LITERACY CLASSES - Pardayev Sobit Abdivali o‘g‘li; Mirzayeva Dilfuza Bahodir qizi (Ustozlar uchun, 2025)
Abstract: Singing in a group (choir) in musical culture lessons in secondary schools is closely related to conducting. In this process, the teacher acts as the leader and conductor of the choir, and at the same time, one of the most important pedagogical tasks is to teach students to sing with an understanding of conducting actions, that is, to acquaint them with basic knowledge of conducting.